Optimization of fertilizer based media for the cultivation of scendesmus species. - MANGAIYARKARASI.A; GEETHA RAMANI.D; NAVEENA .M (International Journal of Pharma and Bio Sciences, 2017)
Microalgae can efficiently utilize CO2 from atmosphere and are responsible for more than 50% of the total global carbon fixation. The algal biomass is a good source of various commercially important compounds. Physiochemical parameters such as light intensity, pH, and temperature are known to influence the growth rate and biochemical composition of the algae. Nutrient composition like Nitrogen and phosphorus of the culture media also influences biomass production. It is not economically viable to use analytical grade nutrients for mass cultivation of microalgae. This investigation was conducted with the aim of providing a simple and inexpensive medium to decrease the cost of large scale production of Scendesmus sp. Various fertilizer based media such as Nitrogen, Phosphorous, and Potash (Potassium) (NPK),Di Ammonium Phosphate(DAP),Urea Superphosphate Trace metals(UST) NPK, DAP, UST have been used for biomass production. As UST medium was found to support maximum biomass productivity, further optimizations of media components of UST medium and physical factors that influence the microalgal growth were optimized. optimized. The concentration of Urea and Phosphate at 522mg/L and 28 mg/L respectively, and the trace metals at the concentration of 1m L L-1 at the of PH 8 and the light intensity of 1700 Lux at room temperature were observed as optimum for the growth of algae. In UST medium, the biomass productivity and the specific growth was found to be 0.4 gL-1d-1 and 0.3(µ) (d-1) respectively and in BG11 medium, the biomass productivity and the specific growth was 0.12 gL-1d-1 and 0.09(µ) (d-1) respectively. A twofold increase in biomass productivity in UST medium compared to BG 11 medium was observed. Thus UST medium can serve as an economically viable medium for the mass production of Scendesmus sp.